Reminiscing African Presence in Text: A Content Analysis of 50 Years of Published Works in Educational Considerations - Ernestina Wiafe (Educational Considerations, 2024)
In an era characterized by evolving perspectives on diversity, inclusion, and decolonization within the domain of education, the exploration of African presence in educational literature emerges as an important endeavor. This study delved into a half-century of published works in Educational Considerations, with a particular focus on texts about and from Africa. Employing a qualitative content analysis methodology, the research traversed a vast corpus of published works spanning five decades. The analysis showed a progressive transition from underrepresentation to an emerging exploration of Africa in Educational Considerations, which signifies the growing acknowledgment of Africa’s invaluable contribution to shaping academia, an essential part of the dialogue surrounding diversity and inclusive representation in educational literature.
Keywords: Reminiscing; African Presence; Content Analysis; Education literature; Diversity; and Inclusion